2017
DOI: 10.1016/j.foreco.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Spatially explicit measurements of forest structure and fire behavior following restoration treatments in dry forests

Abstract: Restoration treatments in dry forests of the western US often attempt silvicultural practices to restore the historical characteristics of forest structure and fire behavior. However, it is suggested that a reliance on non-spatial metrics of forest stand structure, along with the use of wildland fire behavior models that lack the ability to handle complex structures, may lead to uncharacteristically homogeneous rather than heterogeneous forest structures following

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 78 publications
4
60
0
Order By: Relevance
“…Furthermore, the reduction in the perimeter–area ratio suggests that the prevalence of canopy edges has been reduced, indicating increased homogeneity. These results concur with other studies that detected high levels of forest complexity prior to treatment (Cadry ; Ziegler ). In stands with diverse canopy patch sizes prior to treatment, restoration should aim to retain a full range of canopy patch sizes while decreasing total canopy cover.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the reduction in the perimeter–area ratio suggests that the prevalence of canopy edges has been reduced, indicating increased homogeneity. These results concur with other studies that detected high levels of forest complexity prior to treatment (Cadry ; Ziegler ). In stands with diverse canopy patch sizes prior to treatment, restoration should aim to retain a full range of canopy patch sizes while decreasing total canopy cover.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, our low aggregation cases, in which the level of aggregation was no more than random, are probably fairly comparable to some contemporary forests with more homogeneous conditions, either as a result of regularly spaced thinning treatments (for 30% canopy cover cases) or as a result of fire suppression or other land use practices (for 60% canopy cover cases). The broad reduction in fire behavior between our 60% and 30% canopy cover cases, regardless of aggregation pattern, agrees with a number of other studies that demonstrate reduction in fire behavior as a result of fuel treatments [36], including a recent physics-based fire modeling study in similar fuels [63], and reinforces the idea presented in that paper that fuel treatments with aggregated patterns are likely similar to more conventional treatment approaches in reducing fire behavior. Our study showed sensitivity to wind speed, suggesting that fuel treatments are likely limited in their effectiveness under more severe conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Our observed intraspecific aggregation among all species supports the idea that aggregation is the predominant pattern in ponderosa pine-dominated forests [2,6]. After stand-replacing fire, both topography and intraspecific interactions played roles in formation of aggregation.…”
Section: Intraspecific Spatial Patternssupporting
confidence: 84%